A Negishi cross-coupling reaction enables the total synthesis of (+)-stachyflin. Issue 26 (28th June 2018) - Haut, Franz-Lucas; Speck, Klaus; Wildermuth, Raphael; Möller, Kristof; Mayer, Peter; Magauer, Thomas
Abstract: We present a full account on the development of the total synthesis of the antiviral meroterpenoid (+)-stachyflin. The decalin subunit is rapidly accessed by an exo -selective Diels–Alder reaction, whereas the isonindolinone was synthesized via a highly efficient and practical de novo route starting from dimedone. A challenging sp 2 –sp 3 Negishi cross-coupling reaction enabled construction of the crucial C15–C16 bond that connects the arene with the decalin subunit. For the final installation of the cis -decalin framework, a Lewis acid-catalyzed cyclization was applied. Graphical abstract: Image 1